Data for mixed-effects Cox model for moose - Courbin, Nicolas; Fortin, Daniel; Dussault, Christian; Courtois, R. (Dryad Digital Repository, 2014)
Data used to model the risk of patch departure for moose in winter as a function of network connectivity and landscape features (Table 4).